Enduring Wisdom: Traditional Sustainable Livelihood Practices of Indian Tribes - Shandilya, Shivendra; Chaudhary, Dr. Rouchi (Problemy Ekorozwoju, 2026)
This research paper investigates the environmental and cultural knowledge contained within the Traditional Ecological Knowledge (TEK), and Indian Knowledge Systems (IKS) of the Indian tribal communities. The TEK, and IKS of tribes such as the Khasi, Gond, Korku, Apatani, Adi, and Santhal communities, are motivated by Vedic environmental philosophy that embraces coexistence as part of a greater ecosystem through adherence to Rta and Dharma. Both concepts have been software to embed sustainability into local practices with regards to preservation, agriculture, resource management and biodiversity conservation. Direct illustrations of modern sustainability in past practices are evident through sacred grove care, rotational farming practices, and the continued use of ethnomedicinal plants. To support these relationships to sustainability, the TEK, and IKS align with Indo-German Bilateral Cooperation that recognizes twelve of the seventeen UN Sustainable Development Goals (SDGs). It is noted that the TEK, and IKS enshrined in indigenous tribal culture, thought, and relationships are at risk due to factors such as modernization, land alienation, initiation to carve individual property ownership, and gaps in legislated policies and tools to sustain local practice. The commentary from this article is that the TEK, and IKS should shape environmental policy, recognize the ecological and cultural significance of the knowledge systems, and include concepts of documentation to protect intellectual property. This commentary does not acknowledge the community-driven and initiated ways forward to ensure ecological balance, cultural sustainabilities, and sustainability development goals in India.